Continuous and scalable manufacture of aggregation induced emission luminogen fibers for anti-counterfeiting and hazardous gas detecting smart textiles. (July 2021) - Jiang, Qian; Yuan, Hongli; Dong, Kai; Lin, Jia-Horng; Wu, Liwei; Tang, Youhong
Graphical abstract: Highlights: The conjugate electrospinning facilitates the scalable manufacture of fiber. Best fluorescent performance is achieved with optimal spinning parameters. The fluorescence intensity of fiber is proportional to the spinning rate. The fiber reserves 90% fluorescence intensity after stretching and bending. The light-emitting fabrics are proved effective as smart textiles. Abstract: Flexible, lightweight and practical luminous fibers have aroused great interest in the field of smart textiles. In this study, we report flexible aggregation induced emission luminogen (AIEgen) fibers which can be produced in a continuous and large-scale way. Fluorescent nanofibers prepared by conjugate electrospinning are wrapped on the surface of flexible core fiber to form a skin-core AIEgen fiber. The electrospinning parameters including spinning concentration, traction rate, spinning rate and tetraphenylethylene (TPE) concentration were designed and optimized via the non-interactive orthogonal experimental design. The optimized flexible AIEgen fiber retains the excellent mechanical properties of core fiber and is equipped with the fluorescence properties of the wrapped fluorescent nanofibers. In addition, the fabricated AIEgen fibers can still exhibit good fluorescence characteristic after being stretched, bent, washed and rubbed, displaying excellent durability. Different from reported luminescent fibers which required an external power supply or complicated preparation process, the flexible AIEgen fibers fabricated in this study can be prepared continuously in a large-scale way and exhibits effectiveness in clothing display, anti-counterfeiting, information transmission and hazardous gas detection, which shows great application potential for wearable smart textiles.